Study on driver's active emergency response in dangerous traffic scenes based on driving simulator - Ma, Shuai; Xu, Shucai; Song, Jiafeng; Wang, Kejun; Qin, Haoyi; Wang, Ruixiang (Traffic injury prevention, 2024)
A driver's active emergency response in dangerous traffic scenes consists of two parts, including reaction behavior and physiological state. In dangerous traffic scenes, the driver's active emergency response has an important impact on human collision injury. Clarifying the driver's active emergency response is an important prerequisite for the study of human collision injury under nonstandard posture. Therefore, this study investigates the driver's active emergency response in different inevitable collision scenes using driving simulator. A driving simulator with a high-speed camera system and human physiological signal acquisition system was first built. Then, three typical vehicle dangerous collision scenes were developed, including frontal collision, side collision, and rear-end collision. Finally, twenty participants (15 males and 5 females) were recruited for a driving experiment, and their active emergency responses were recorded and analyzed. All subjects would rotate the steering wheel to the left or right in the active emergency state, and the rotation of the hand would also cause the subject's upper body to tilt in the same direction. The maximum angle for male subjects to rotate the steering wheel was 59.98°, while for the female subjects, it was 44.28°. In addition, the maximum grip force between the male subjects and the steering wheel was 280.5 N, compared to 192.5 N for female subjects. Compared to the female participants, the male participants not only have a greater rotation angle and a greater grip force on the steering wheel, but also have greater pressure on the brake pedal, and the foot moves quickly from the accelerator pedal to the brake pedal and presses the brake pedal. Drivers have different active emergency responses to different vehicle collision scenes. Quantitative statistics of driver's active emergency response will have important guiding significance for the analysis of the impact of human active emergency response on human injury characteristics in subsequent vehicle collision experiments.